Experimental Investigation on Cutting Forces in Sustainable Hard Milling of Hardox 500 Steel Under Al2O3/MoS2 Hybrid Nanofluid MQCL Environment - Tran The Long (Lubricants)
Hardox 500 is a special low-alloy, martensitic steel possessing extraordinary wear resistance, high hardness, and high ductility; thus, it has been widely used in many industrial applications. Nevertheless, this type of steel has a low machinability and is grouped among the difficult-to-machine materials. Hence, this paper’s objective was to study its hard milling performance under minimum quantity cooling lubrication (MQCL) conditions using an Al2O3/MoS2 hybrid nano cutting oil. The Box–Behnken response surface methodology was used to investigate the effects of the nanoparticle concentration (NC), cutting speed (v), and feed rate (f) on the total cutting force F and cutting force coefficient Fy/Fz. The obtained results indicate that the cutting efficiency of Hardox 500 steel was improved thanks to the enhancement in cooling lubrication from the MQCL using the Al2O3/MoS2 hybrid nano cutting oil. The applicability of vegetable oil and coated carbide inserts is thus extended to the hard milling of difficult-to-cut materials. Moreover, the provision of the appropriate ranges and optimal set of investigated variables obtained in this paper will be useful guides for technologists and further studies. Concretely, NC = 0.5–0.7%, v = 110–115 m/min, and f = 0.08–0.10 mm/tooth are the optimal set for the total cutting force F, while NC = 0.5%, v = 138–140 m/min, and f = 0.08–0.09 mm/tooth are suggested for the cutting force coefficient Fy/Fz.